Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society 1992
DOI: 10.1109/iembs.1992.5761830
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of scaling factors in electrically evoked myoelectric signals

Abstract: During a sustained contraction the surface my oelectric signal undergoes amplitude scaling (by a factor h), due to reduction or loss of motor unit B, dinn potentials, and time scaling (hy a factor k) due to reduction of muscle fiber CV and other fac tors. These changes are particularly evident in the responses evoked by electrical stimulation (M-waves) when stimulation rate is above 30 or 35 Hz. The time expansion factor corresponds to a frequency com pression factor of the signal's power spectral density (PSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 0 publications
1
86
0
4
Order By: Relevance
“…RMS) and frequency (i.e. mean and median frequencies) parameters (Merletti & Knaflitz, 1992). For the contractions during the ECC and CON protocols, RMS was calculated only for the 100 ms isometric contraction immediately preceding the 20 ms isokinetic contraction.…”
Section: Animalsmentioning
confidence: 99%
“…RMS) and frequency (i.e. mean and median frequencies) parameters (Merletti & Knaflitz, 1992). For the contractions during the ECC and CON protocols, RMS was calculated only for the 100 ms isometric contraction immediately preceding the 20 ms isokinetic contraction.…”
Section: Animalsmentioning
confidence: 99%
“…In our study, the pain induction protocol has shown that M waves had their amplitudes changed. Some authors understand that a change in M wave amplitude is related to changes in pH, temperature and muscle fibers diameter 10,11 . M wave valley is exactly the point were there is major change in membrane patency and fibers contract due to a fast ions inflow caused by this patency change.…”
Section: Discussionmentioning
confidence: 99%
“…Amplifier saturation is a common problem in electrical stimulation systems [14,16,19], and arises when the actual voltage (comprising artifacts and neural activities) exceeds the saturation limit of the stimulation hardware. Although in this work we have considered stimulation regimes that did not lead to saturation, we emphasize that our method would be helpful to deal with saturated traces as well: indeed, in opposition to naive approaches that would lead to no other choice than throwing away entire saturated recordings, our modelbased approach enables a more efficient treatment of saturation-corrupted data.…”
Section: Limitationsmentioning
confidence: 99%
“…However, these methods fail when used on data corrupted by stimulation artifacts. Although technological advances in stimulation circuitry have enabled recording with significantly reduced artifacts [14][15][16][17][18], identification of neural responses from artifact-corrupted recordings still presents a challenging task-even for human experts-since these artifacts can be much larger than spikes [19], overlap temporally with spikes, and occupy a similar temporal frequency band as spikes.…”
Section: Introductionmentioning
confidence: 99%